Loading method for tractor rotary tillage load spectrum based on extreme load retention resampling - Wang, Yu; Wang, Ling; Wang, Shumao; Zhao, Junsheng; Zhang, Yajun; Wen, Changkai; Ma, Tiehua (International Journal of Agricultural and Biological Engineering, 2025)
Conducting bench tests for tractors according to the load spectrum is essential for assessing their reliability and fatigue durability. However, achieving an accurate replication of field operating conditions poses challenges due to the disparity in response characteristics between the tractor bench loading system and the frequency data of the load spectrum. Consequently, discrepancies in test results arise. To mitigate this challenge, this study proposes a loading method for the tractor rotary tillage load spectrum based on extreme load retention resampling. Firstly, a tractor rotary tillage load acquisition test was conducted, and a one-time-extrapolated load spectrum was compiled based on the Peak Over Threshold model. Considering the characteristics of rotary tillage operations, the tractor rotary tillage load spectrum loading bench was developed, which primarily includes the Power Take-Off (PTO) loading system and the suspension loading system. On this basis, a rotary tillage load spectrum loading system based on a Fuzzy-PID controller was proposed to realize the dynamic loading of the rotary tillage load spectrum. The dynamic response characteristics of the loading bench were analyzed based on a simulation model, and the results showed that the loading bench can achieve dynamic loading of load spectra with frequencies below 25 Hz. To match this characteristic, a load spectrum resampling method based on extreme load retention was proposed to resample the rotary tillage load spectrum. Based on the retention of the load spectrum fatigue damage, a resampled rotary tillage load spectrum with a resampling ratio of 3 was obtained, with a loading frequency of 20.98 Hz. Finally, the tractor rotary tillage loading test was conducted based on the resampled rotary tillage load spectrum. The test results demonstrated that the loading bench effectively replicated the resampled rotary tillage load spectrum. For the PTO torque load spectrum, the average error is –7.53%, with a delay of 30 ms, and for the suspension load spectrum, the average error is –2.48%, with a delay of 22 ms. The result indicated that the resampled load spectrum can well match the dynamic characteristics of the loading bench. This research can serve as a practical reference for implementing tractor bench tests grounded in load spectra. Keywords: spectrum, Power Take-Off, Fuzzy-PID controller, extreme load retention resampling, bench test DOI: 10.25165/j.ijabe.20251804.9418 Citation: Wang Y, Wang L, Wang S M, Zhao J S, Zhang Y J, Wen C K, et al. Loading method for tractor rotary tillage load spectrum based on extreme load retention resampling. Int J Agric & Biol Eng, 2025; 18(4): 128–138.